Intensionality - Kahle, Reinhard 1967- (Cambridge University Press, 2016)
Since their inception, the Perspectives in Logic and Lecture Notes in Logic series have published seminal works by leading logicians. Many of the original books in the series have been unavailable for years, but they are now in print once again. This volume, the twenty-second publication in the Lecture Notes in Logic series, will launch a discussion about the concept of intensionality in philosophy, logic, linguistics and mathematics. These articles grew out of a workshop held at the University of Munich in October, 2000. Some articles address philosophical issues raised by the possible worlds approach to intensionality; others are devoted to technical aspects of modal logic. The volume highlights the particular interdisciplinary nature of intensionality with articles spanning philosophy, linguistics, mathematics and computer science.